2018
DOI: 10.18632/oncotarget.25230
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNAs as biomarkers in diffuse large B-cell lymphoma: a systematic review

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive and heterogeneous malignancy, with highly variable outcomes among patients. Although classification and prognostic tools have been developed, standard therapy still fails in 30-40% of patients. Hence, identification of novel biomarkers is needed. Recently, circulating microRNAs (miRNAs) have been suggested as non-invasive biomarkers in cancer. Our aim was to review the potential role of circulating miRNAs as biomarkers for diagnosis, classification, progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…In lymphoma, Lawrie et al [ 207 ] showed miR-155, miR-210, and miR-21 in high levels in serum from DLBCL patients compared with healthy controls’ sera. Moreover, high miR-21 expression was associated with RFS [ 207 ], which was later confirmed by Chen et al [ 220 ] in an independent cohort; thus far, it is the only circulating miRNA in DLBC that has shown consistent results and is now considered a biomarker for diagnosis [ 221 ].…”
Section: Mirnas In Clinicsmentioning
confidence: 82%
“…In lymphoma, Lawrie et al [ 207 ] showed miR-155, miR-210, and miR-21 in high levels in serum from DLBCL patients compared with healthy controls’ sera. Moreover, high miR-21 expression was associated with RFS [ 207 ], which was later confirmed by Chen et al [ 220 ] in an independent cohort; thus far, it is the only circulating miRNA in DLBC that has shown consistent results and is now considered a biomarker for diagnosis [ 221 ].…”
Section: Mirnas In Clinicsmentioning
confidence: 82%
“…MiR-494 was chosen for further evaluation as the archetypal exemplar of moMDSC-related miRNA. Despite not showing consistent DE, miR-21 and miR-155 were also included due to the findings in previous studies that showed they are enriched in DLBCL cell-lines and are elevated in the circulation at diagnosis [ 13 , 28 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been repeatedly recognized that c-f and PBMC miR-21 expression levels are elevated at diagnosis in DLBCL, with conflicting results regarding circulating miR-21's prognostic value [ 13 , 28 – 31 ]. To our knowledge, no studies of sequential c-f miR-21 once immuno-chemotherapy has been initiated and comparison with interim-PET/CT have been performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many miRNAs have been identified as biomarkers of B-cell lymphoma. 22 , 23 Schneider et al. 17 revealed that miR-28 expression is downregulated in B-cell lymphomas, suggesting that silencing of miR-28 will contribute to lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%